Disease management in regenerative cropping in the context of climate change and regulatory restrictions - Newton, Adrian C. (2024)
Regenerative agriculture as a term and concept has gained much traction over recent years. Many farmers are convinced that by adopting these principles they will be able to address the triple crisis of biodiversity loss, climate change, and food security. However, the impact of regenerative agriculture practices on crop pathogens and their management has received little attention from the scientific community. Significant changes to cropping systems may result in certain diseases presenting more or less of a threat. Shifts in major diseases may have significant implications regarding optimal integrated pest management (IPM) strategies that aim to improve profitability and productivity in an environmentally sensitive manner. In particular, many aspects of regenerative agriculture change risk levels and risk management in ways that are central to effective IPM. This review outlines some of the challenges, gaps, and opportunities in our understanding of appropriate approaches for managing crop diseases in regenerative cropping systems.